PENGENALAN MANFAAT DAN PENGUJIAN pH JUS APEL FUJI DAN JUS ALPUKAT UNTUK KESEHATAN - Ni Made Sukma Sanjiwani; I Wayan Sudiarsa; Ni Putu Ayu Mirah Mariati; Agung Ari Chandra Wibawa; I Wayan Surya Rahadi; Puguh Santoso (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
One of the herbal drinks that have positive effects on health is juice. The chief executive of the community service decided to give an introduction to the banjar abasan community in Singapadu Tengah village because the abasan community pays less attention to their body health. They also do not know how to test the pH of fuji apple and avocado juice for health. In this service, an introduction to the benefits and negative effects of fuji apple and avocado juice was carried out in the form of socialisation and an introduction to making and testing the pH of fuji apple juice and avocado juice in the form of training demonstrations. This service begins with giving a pre-test and ends with giving a post-test in order to hone the community's knowledge related to the knowledge that has been given in this community service. This service is very beneficial for the abasan community because they are given knowledge related to apples and avocados and the negative effects of consuming them excessively and in the wrong time, the benefits of fuji apple juice and avocado juice. The abasan community also gained knowledge on how to make and test the pH of fuji apple juice and avocado juice and the benefits of testing the pH of the juice. Based on the results of the pretest and postest, most of the service participants really understood about this service and had a great desire to become avocado juice and fuji apple juice entrepreneurs because the manufacturing process was easy and the selling price was affordable.